Time to complete contemporary dental procedures - estimates from a cross-sectional survey of the dental team - Christian Bannister; Anwen Louise Cope; Anup Karki; Paul Harper; Sarah Peddle; Brenda Walters; Michael Allen; Ivor Gordon Chestnutt (BMC, 2023)
Abstract Background There are few contemporary studies on the time taken to complete dental procedures, those most heavily relied on in the United Kingdom date back to 1999. Objectives This work aimed to establish how long members of the dental team took to complete specific dental procedures, relevant to their scope of practice. Methods Data were collected via a purposive sample of 96 dentists, dental hygienists/therapists and dental nurses. Via an online survey, participants were asked to state the mean, minimum and maximum time they estimated that they took to complete individual dental procedures. Results The mean time taken to complete procedures common to both dentists and dental hygienists/therapists ranged from 3.7 to 4 min respectively for clinical note reading prior to seeing patients to 30.1 and 28 min to undertake root surface debridement. There were no significant differences between the time taken by dentists and dental hygienists/therapists to treat adult patients. However, in all but one procedure, dental hygienists/therapists reported taking longer (p = 0.04) to treat child patients. Conclusions The data provided here represent an up to date assessment of the time taken to complete specific tasks by different members of the dental team. These data will be of value to service planners and commissioners interested in evolving a dental care system that employs a greater degree of skill-mix and preventively oriented care.